EVALUASI PROGRAM LAYANAN PENGADUAN DIGITAL PERUNDUNGAN SISWA DI DENPASAR - Yani, Erna; Patimah, Siti; Saputra, M. Indra; Warisno, Andi; Putri, Ni Putu Laksmi Resti (FIKRAH, 2025)
This study evaluates the anti-bullying digital complaint service program "SiLaMis" at SD Negeri 11 Padangsambian Denpasar, Bali, which aims to create a safe and comfortable learning environment for students. Using the CIPP program evaluation model, this study found that the SILAMIS program is aligned with the school’s vision, has quality resources, innovative features, and adequate training. This program is also carried out according to procedures and is effective in suppressing bullying cases, and shows a positive impact on reducing bullying cases, increasing student comfort, and service user satisfaction. The results of the study recommend that the SILAMIS program be continued by strengthening the existing advantages and improving the quality and efficiency of the program.